The Role of Working Mothers in Forming the Independent Attitude of Early Children at the Time Covid-19 Pandemic - Mutmainah, Naeli; Ahyani, Hisam (PIAUD Universitas Islam Negeri Sunan Kudus, 2022)
Today, the role of a working mother is very important in forming an independent attitude in early childhood, starting from the parenting pattern, as well as the supporting and inhibiting factors, especially during the COVID-19 pandemic as it is today. This type of research was analyzed using descriptive qualitative research methods with data collection techniques through observation, interviews and documentation. The findings of this study are that the role of a working mother in forming an independent attitude in early childhood education in Raudhatul Athfal (RA) Nurul Huda Banjar City is the role of a motivator, supervisor, educator, counselor, and role model. The most appropriate parenting pattern applied by working mothers in shaping children's independent attitudes is democratic parenting. The implication of this research is that the factors that support the formation of independent attitudes of children by working mothers in Raudhatul Athfal (RA) Nurul Huda Banjar City during the COVID-19 pandemic include: environment, love and affection, and parenting. While the inhibiting factors are: the child's mood, inadequate parenting, peers or playmates, time and opportunity. The practical implication of this research is that the role of a working mother can form an independent attitude for early childhood..